FoodCraft: design of a precision agriculture system with IoT in indigenous communities in rural areas with difficult Internet access in the department of Cauca-Colombia - Orozco Monje, Juan Sebastián (2023)
Nowadays, many countries have been implementing precision agricul-ture systems based on the Internet of Things (IoT) as they are useful tools to manage and monitor crop information for farmers. There is a wide diversity of approaches that help and facilitate producers to manage their agricultural land. IoT systems provide capabilities to adapt to the user's environment, for example by sensing data through wireless sensors or other devices. In agriculture, they can support the early detection of possible crop alterations and prevent production losses, thus improving the quantity and quality of the harvest, considering that each crop requires a personalized intervention. This research aims to propose an IoT system for the management and monitoring of the agricultural lands of the indigenous communities of Cauca, where Internet access is limited. The system adapts to the needs of the user, their agricultural and environmental information, time, location and traditional practices. This article introduces the IoT architec-ture and models, which were used to implement and test a prototype called Food-Craft. For the design of this system, there is satellite communication between IoT points with difficult access to the Internet. On the other hand, all sensor data is successfully received by the Arduino mega and sent to the database with the ESP8266 so that it can be accessed through the integrated Android app and web-site.